The Effect of Training the Nine Enneagram Personality Types on Spouse Selection Criteria and Marital Attitude of Single Girls - Marzieh Memarzadeh; Anahita Khodabakhshi-koolaee; Mahnaz Khatiban (Hamadan University of Medical Sciences, 2017)
Background and Objectives: The foundation of any society is built upon marriage and starting a family. However, marriage is a complex and challenging issue, success in which is hinged upon various factors such as attitude towards marriage. This study was carried out to evaluate the effect of training the 9 Enneagram personality types on spouse selection criteria and attitude towards marriage in single grils. Materials and Methods: This quasi-experimental study with a pretest-posttest design and control group was performed on all the third-grade high school female students in the District 14 of Tehran, Iran, during 2015-16 academic calendar. The subjects were selected through multistage cluster sampling from two schools in the mentioned district. A total of 30 students were selected and randomly divided into control and experimental groups. The data collection tools consisted Preference Criteria of Spouse Selection Inventory (PCSSI) and Marital Attitude Scale (MAS). The intervention group received ten 90-minute sessions (once a week). To analyze the data, analysis of covariance was run in SPSS, version 22. Results: After the intervention, there was a significant difference between the intervention and control groups in terms of overall attitude and cynical attitude towards marriage and the general, procedural, and content spouse selection criteria (P<0.05). However, there was no significant difference between the two groups with respect to idealistic attitude towards marriage at the post-intervention stage (P>0.05). Conclusions: According to the results, training the 9 Enneagram personality types was effective in marital attitude and spouse selection criteria of girls.